COSTS OF THE HEALTH CARE IN RUSSIA ASSOCIATED WITH SMOKING - A. V. Kontsevaya; A. M. Kalinina (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To analyze costs of health care in Russia associated with smoking in 2009. Material and methods. Cardiovascular diseases, cancers and chronic obstructive pulmonary diseases (COPD) were included in the analysis. Calculation was performed on the basis of the relative risks of diseases associated with smoking, and obtained from foreign surveys, official statistics on morbidity and health system resources expenditure, and costs of health-seeking in line with state program of guaranteed free medical care.  Results. In 2009 total costs of the health care system associated with smoking exceeded RUR 35.8 bln. It corresponded to 0.1% of gross domestic product in Russia in 2009. The costs structure was the following: hospitalization – RUR 26.2 bln, emergency calls – RUR 1.4 bln, and outpatient health-seeking – RUR 8.2 bln. Costs of outpatient pharmacotherapy were not included into analysis because of lack of baseline data needed for calculations. Cardiovascular diseases caused 62% of the health care costs associated with smoking, cancers – 20.2%, and COPD – 17.8%. Conclusion. The smoking in Russia is associated with significant health care costs. It makes needed resources investment in preventive programs to reduce smoking prevalence.